1995
DOI: 10.1080/09349849509409554
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Mapping of Pore Fraction Variations in Silicon Nitride Using an Ultrasonic Contact Scan Technique

Abstract: An ultrasonic scan procedure using the pulse-echo contact configuration was employed to obtain maps of pore fraction variations in sintered silicon nitride samples in terms of ultrasonic material properties. Ultrasonic velocity, attenuation coefficient, and reflection coefficient images were obtained simultaneously over a broad band of frequencies (e.g., 30 to 110 MHz) by using spectroscopic analysis. Liquid and membrane (dry) coupling techniques and longitudinal and shear-wave energies were used. The major re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…It was concluded that the buffer-rod method [30][31][32] is not practical to determine material attenuation under normal laboratory conditions. While it may have worked in situations where advanced sample preparation facilities and precision alignments were available [33][34][35][36][37], their results still showed unacceptably large differences among them, as discussed in Section 1. It appears that the refraction occurring at the buffer-sample interface needs to be examined as the source of the difficulties encountered.…”
Section: Buffer-rod Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was concluded that the buffer-rod method [30][31][32] is not practical to determine material attenuation under normal laboratory conditions. While it may have worked in situations where advanced sample preparation facilities and precision alignments were available [33][34][35][36][37], their results still showed unacceptably large differences among them, as discussed in Section 1. It appears that the refraction occurring at the buffer-sample interface needs to be examined as the source of the difficulties encountered.…”
Section: Buffer-rod Methodsmentioning
confidence: 99%
“…However, for Si 3 N 4 , Evans et al [33] obtained attenuation coefficients ranging from 150 to 5300 dB/m at 11 to 53 MHz. In contrast, Generazio [34] reported 235 dB/m at 60 MHz and Roth et al [36] reported 130 to 1020 dB/m at 30 to 110 MHz (with 480 or 696 dB/m at 50 or 60 MHz). These results from two distinguished laboratories revealed large discrepancies of more than a factor of ten, highlighting the difficulty of the buffer-rod method.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Simple theory was found useful in predicting the velocity change for low porous material. 1,2 For fluid statured porous foam, two types of ultrasonic waves: slow and fast waves can be generated. 36 This phenomenon has been predicted by Biot.…”
Section: Introductionmentioning
confidence: 99%